2021
DOI: 10.3390/toxics9040078
|View full text |Cite
|
Sign up to set email alerts
|

nLossFinder—A Graphical User Interface Program for the Nontargeted Detection of DNA Adducts

Abstract: DNA adductomics is a relatively new omics approach aiming to measure known and unknown DNA modifications, called DNA adducts. Liquid chromatography–tandem mass spectrometry (LC-MS/MS) has become the most common method for analyzing DNA adducts. Recent advances in the field of mass spectrometry have allowed the possibility to perform a comprehensive analysis of adducts, for instance, by using a nontargeted data-independent acquisition method, with multiple precursor m/z windows as an inclusion list. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…Early DNA adductomics primarily utilized triple quadrupole instrumentation to perform neutral loss screening, 30 whereas more recent studies have taken advantage of HRMS, 4 which allows performing different types of acquisition modes such as DDAtriggered neutral loss, 9 wide selected ion monitoring tandem mass spectrometry (Wide-SIM/MS2), 10 and data independent acquisition (DIA). 6 Whereas DDA selects specific precursor ions for fragmentation resulting in clean MS2 spectra, DIA (or MS E ) fragments the entire range of ions, requiring elaborate data analysis software for the investigation of the spectra, 6 and a supplementary MS2 targeted acquisition for confirming the identity of the compound. However, the selective approach of DDA carries the risk of losing the fragmentation of the least abundant compounds.…”
Section: Acquisition Mode and Identification Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Early DNA adductomics primarily utilized triple quadrupole instrumentation to perform neutral loss screening, 30 whereas more recent studies have taken advantage of HRMS, 4 which allows performing different types of acquisition modes such as DDAtriggered neutral loss, 9 wide selected ion monitoring tandem mass spectrometry (Wide-SIM/MS2), 10 and data independent acquisition (DIA). 6 Whereas DDA selects specific precursor ions for fragmentation resulting in clean MS2 spectra, DIA (or MS E ) fragments the entire range of ions, requiring elaborate data analysis software for the investigation of the spectra, 6 and a supplementary MS2 targeted acquisition for confirming the identity of the compound. However, the selective approach of DDA carries the risk of losing the fragmentation of the least abundant compounds.…”
Section: Acquisition Mode and Identification Approachmentioning
confidence: 99%
“…Whereas traditional -omics sciences rely on extensive existing database and software support, DNA adductomics is in a developmental phase. 5,6 A few studies have been published with the aim of building DNA adduct databases, which can be used as a tool for DNA adduct profiling. [7][8][9] A few other studies reported the development of untargeted DNA adductomics methods for identification of unknowns.…”
Section: ■ Introductionmentioning
confidence: 99%
“…DNA adductomics has been applied in studies of cancer and ecotoxicology . For the detection of unknown DNA adducts, a method based on the neutral loss of 2′-deoxyribose from digested DNA samples has been used. , Recently, algorithms for the detection of such adducts in liquid chromatography–mass spectrometry (LC-MS) analysis have been created. , For protein adducts, adductomic approaches have been developed for serum albumin and hemoglobin (Hb) . Rappaport and collaborators have developed a method for the analysis of Cys34 adducts in serum albumin as 21-mer peptides after tryptic digestion .…”
Section: Introductionmentioning
confidence: 99%
“…HPLC/ESI-MS/MS methodologies have significantly broadened the range of applications related to modified amino acids in general. The possibility to determine and characterize amino acid adducts to trace exposure to reactive electrophilic chemicals across the general population, such as from dietary intake or workplace environments, has paved the way for adductomics [24][25][26][27]. A highly selective MS platform that combines high-resolution, high m/z accuracy and ion fragmentation (tandem HRMS) would increase the possibility to identify and measure such trace levels of adducts, as has been reported in studies with DNA adducts [28][29][30].…”
Section: Introductionmentioning
confidence: 99%